Nutraceuticals for Age-Related Macular Degeneration: Formulation Optimization Focused on Safety - E. K. Pedanova (Oftalʹmologiâ, 2022)
Age-related macular degeneration (AMD) is a multifactorial disease, with oxidative stress as a main pathogenetic factor in the development and progression. Large clinical trials have shown that the additional intake of vitamins and minerals in high doses reduce the risk progression to advanced wet AMD by 25 %. Some of these powerful antioxidants are not synthesized in the human body and can only be obtained with food as part of dietary supplements. However, patients with AMD, belonging to the older age group, often have comorbid conditions, for which they are used to take appropriate drug and vitamin therapy for a long time, as well as they have malnutrition of varying severity. Additional intake of high doses of ophthalmic vitamin-mineral complexes can lead to side effects due to overdose and possible disorders of drug absorption due to concomitant pathology. The article presents the results of the AREDS 2 study and a number of other clinical trials that studied long-term intake of vitamins and minerals in dosages similar to the AREDS 1 formula, containing vitamin C (500 mg), vitamin E (400 international units), beta-carotene (15 mg), zinc (80 mg as zinc oxide) and copper (2 mg as copper oxide). The cited works show that long-term intake of high dosages of some vitamins in elderly patients with severe concomitant diseases and a history of smoking can lead to undesirable consequences for the eye and other body systems. Potential side effects include an increased risk of glaucoma and cataract, an increased risk of prostate cancer in healthy men, an increased risk of lung cancer in former smokers, and an increased risk of cardiovascular disease in postmenopausal women with diabetes. Thus, high dosages of vitamins and minerals in nutraceuticals should be administered with great caution, and a reduction in dosages to the recommended intake rates when switching to long-term intake may be considered. One of the possibilities for increasing the bioavailability of active substances in the composition of dietary supplements can be a microencapsulation.